PROFESIONALISASI GURU PENDIDIKAN AGAMA KATOLIK DI INDONESIA: ANTARA SPIRITUALITAS PANGGILAN DAN PENGAKUAN PROFESIONAL - Luwing, Yosefa; Lorensius, Lorensius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study critically examines the professionalization of Catholic Religious Education (CRE) teachers in Indonesia, revealing an epistemological tension between pedagogical rationality and faith formation. Using a narrative literature review combined with discourse analysis of the 2025 Self-Study Module: Professional Content for CRE, the findings show the dominance of secular-pedagogical discourse that prioritizes learning design, materials, and assessment, while the dimension of faith-based pedagogy and spiritual vocation remains marginal. The study introduces Faith-Based Pedagogical Content Knowledge (FBPCK) as a holistic framework integrating pedagogical competence, spiritual depth, and pastoral identity. It recommends reforming certification modules to include reflective, spiritual, and pastoral formation through guided reflection, spiritual accompaniment, and practice-based portfolios grounded in faith-based professionalism.